(untitled) (Journal of Hama University, 2020)
The study aimed to know the effectiveness of using mind maps in achieving students and reducing the burden of knowledge in biology and earth. The study population consisted of all seventh grade students in the Nasir Shura School in Damascus in the academic year 2019-2020 and the research sample consisted of (48) students. To achieve the goal of the study, the researcher designed mental maps and achievement test, in addition to using the measure of cognitive burden of Dr. Helmy Al-Fil. The semi xperimental approach was used. The researcher reached the following results: - There are statistically significant differences between the mean scores of students of the experimental and control groups in the post application of the achievement test for the benefit of the experimental group students. - There are statistically significant differences between the mean scores of students of the experimental and control groups in the post application of the measure of cognitive burden in favor of students of the experimental group. - There were no statistically significant differences between the mean scores of students of the experimental group on the scale of cognitive burden according to the gender variable (male, female).